HUBUNGAN ANTARA JUMLAH LIMFOSIT TCD4+ DENGAN GANGGUAN FUNGSI KOGNITIF PADA PASIEN TERINFEKSI HIV - Rilia Datan Sampepajung; Audry Devisanty Wuysang; Abdul Muis (PERDOSNI, 2019)
CORRELATION BETWEEN QUANTITY OF CD4+ T LYMPHOCYTE AND COGNITIVE IMPAIRMENT IN PATIENTS WITH HIV INFECTIONABSTRACTIntroduction: CD4+T lymphocyte is a T-lymphocyte that has CD4 glycoprotein on its surface. The quantity of CD4+ T lymphocyte is associated with cognitive function impairment.Aim: To determine the correlation between the quantity of CD4+ T lymphocyte with the cognitive function impairment in patients infected by human immunodeficiency virus (HIV).Methods: This is a cross-sectional study on HIV patients at Wahidin Sudirohusodo Hospital, Makassar from October to December 2018. Cognitive function was assessed using Montreal Cognitive Assessment of Indonesian version (MoCA-Ina) and all infected HIV patients’ CD4+ T lymphocyte was counted through blood laboratory examination. The data processing used SPSS program.Results: There were 40 subjects with male majority (70%). Most subjects (75%) had low count of CD4+ T lymphocytes (<200cel/µL) and most of them (72.5%) had cognitive function impairment.Discussion: The CD4+T lymphocyte was associated significantly with executive and memory impairment in patients with HIV.Keywords: CD4+ T lymphocyte, cognitive impairment, HIVABSTRAKPendahuluan: Limfosit TCD4+ adalah limfosit T yang memiliki glikoprotein CD4 pada permukaan selnya. Jumlah limfosit TCD4+ telah diketahui berhubungan dengan gangguan fungsi kognitif.Tujuan: Mengetahui hubungan antara jumlah limfosit TCD4+ dengan gangguan fungsi kognitif pada pasien terinfeksi human immunodeficiency virus (HIV).Metode: Penelitian observasional dengan rancangan potong lintang terhadap pasien yang terinfeksi HIV di RSUP Dr. Wahidin Sudirohusodo, Makassar pada bulan Oktober-Desember 2018. Subjek dinilai fungsi kognitif menggunakan Montreal Cognitive Assessment versi Indonesia (MoCA-Ina) dan penghitungan jumlah limfosit TCD4+. Pengolahan data menggunakan program SPSS.Hasil: Terdapat 40 subjek yang mayoritas (70%) laki-laki. Terdapat 75% subjek memiliki kadar limfosit TCD4+ yang rendah (<200sel/µL) yang sebagian besarnya (72,5%) mengalami gangguan fungsi kognitif.Diskusi: Jumlah limfosit TCD4+ memiliki hubungan yang signifikan dengan komponen eksekutif dan memori dari fungsi kognitif pada pasien yang terinfeksi HIV.Kata kunci: Gangguan kognitif, HIV, limfosit TCD4+